Application of Naive Bayes Method For Diagnosis of Pregnancy Disease - Embun Fajar Wati; Budi Sudrajat (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The risk of pregnancy can be known by early detection of pregnancy with risk factors, so that health workers can know more about treatment. In diagnosing a disease in the field of medicine requires tools such as the application of artificial intelligence, one of which is an expert system. One method that can be applied in expert systems is naive bayes. In this study, naive bayes for the process of diagnosing the disease during pregnancy was done by including symptoms that appear in pregnant women. The stage of research is the collection of data from previous research journal articles with the same theme, but different methods and other journal articles with the same theme and different from the naive bayes method. The next stage is data analysis with naive bayes calculations of patient symptoms and validation, namely comparing the results of naive bayes calculations with expert calculations. The results obtained were 14 patients out of 20 patients, which is 70% have the same results between experts with calculations with naive bayes. The results showed that the calculation of symptoms with naive bayes was sufficient to give valid and feasible results to use